CHERNOBYL ACCIDENT AND BRYANSK REGION POPULATION DOSE LEVELS FROM PLUTONIUM ISOTOPES - N. S. Shvydko; E. B. Ershov (Радиационная гигиена, 2017)
Exposure doses estimations from plutonium isotopes are given for population living on the territories of Bryansk region contaminated after the Chernobyl accident. For calculations model representations of the plutonium migration in the system soil-man are used. Effective dose from inhalation intake of resuspended activity for population and agricultural machine operators (critical group) is investigated. It is shown that expected annual effective dose due to dust lifting from the contaminated ground surface doesn't exceed 5 µSv for population and 30 µSv for agricultural machine operators (for 1992). Exposure doses were additionally estimated basing on autopsy material radiochemical analysis, which permitted to obtain plutonium isotopes concentration in the organs and tissues of inhabitants of contaminated territories. It was established that annual effective dose from plutonium acquired in 1986-1992 is about 25 µSv.